An Analysis of Productive Zakat Implementation from the Perspective of Shariah Enterprise Theory: A Case Study of Baznas Sukabumi City - Ulum, Wildan Fathul; Sujatna , Yayat (Journal of Islamic Economics and Finance Studies, 2025)
Zakat as a form of worship is governed by Sharia law, and its management must prioritize adherence to Sharia principles over purely economic considerations. This study aims to analyze the implementation of productive zakat for micro, small, and medium enterprises (MSMEs) by Baznas (National Zakat Agency) of Sukabumi City, using the framework of Sharia Enterprise Theory (SET). A descriptive qualitative approach was employed, utilizing interviews, observations, and document analysis. The data analysis process involved data reduction, data display, and conclusion verification. The findings reveal that the productive zakat program is implemented in six distinct stages. Among these, the verification and field review stages, as well as the monitoring and mentoring stages, emerged as the most critical. The study concludes that the program fulfills all dimensions of the Sharia Enterprise Theory, namely accountability to Allah SWT, to direct stakeholders, to indirect stakeholders, and to the environment. However, the research also identifies areas for improvement, particularly in accountability to indirect stakeholders. This is reflected in the limited progress of mustahik-run businesses and the suboptimal dissemination of Baznas reports. Website accessibility and public engagement efforts, such as outreach in open community spaces, remain limited. The study underscores the need to strengthen accountability mechanisms for indirect stakeholders, especially mustahik (beneficiaries) who receive microenterprise funding. It also highlights the importance of enhancing the visibility of Baznas' reporting activities through improved utilization of digital platforms—such as websites and social media—and through regular public outreach initiatives.